Rectifying and Negative Differential Resistance Behaviours Induced by Intermolecular Interaction in Molecular Device - Aruna Priya1, P.; Preferencial Kala2, C.; John Thiruvadigal2, D. (Asian Journal of Chemistry, 2013)
By applying extended Huckel theory in combination with non equilibrium Greens function formalism, we investigate the transport properties of the molecular device with a donor-acceptor molecular complex sandwiched between two electrodes. In the benzene ring, OCH3 and CN group have been substituted and used spacers such as CH2CH2 between the donor and acceptor subunits to form an intramolecular donor spacer acceptor (D-S-A) rectifier. The molecule is attached to two gold leads (111). Calculated current-voltage curves show the pronounced rectification behaviour which is due to the asymmetric shift of the perturbed molecular energy levels under bias voltage. A molecule consisting of three aromatic phenyl rings in series exhibits the negative differential behaviour. The two hydrogen atoms of the middle ring are substituted by acceptor group NO2 and donor group NH2, while the whole molecule is chemisorbed onto the contact surfaces of gold leads. Simulated results show that a negative differential resistance under applied bias is observed which is induced by the orbital match of molecule and electrodes as well as intermolecular charge transfer.